Migration of Hop Polyphenols in Beer Technology: Model Solution for Various Hopping Methods - Marina V. Gernet; Irina N. Gribkova; Olga A. Borisenko; Maxim A. Zakharov; Varvara A. Zakharova (Техника и технология пищевых производств)
Introduction. The research featured the effect of various hopping conditions on the content of polyphenolic compounds associated with the extraction and biotransformation of hop compounds. This mechanism is responsible for uncharacteristic beer flavor in the traditional production method. The research objective was to study the migration routes, influence factors, and changes in the content of hop polyphenols in model experiments in order to reduce various factors in the production process chain. The experiment was important from the point of view of identifying the polyphenols contribution to the beer colloidal system. Study objects and methods. The study involved granulated aromatic hop of Tetnanger variety harvested in 2019, aqueous and 4% aqueous-alcoholic solutions simulating the wort and young beer liquid phase, and brewing yeast Sacharomyces cerevisiae of races Rh (lager) and Nottingham (ale). The work used the generally accepted methods for assessing the content of polyphenolic compounds. Results and discussion. The research established various factors that affected the migration of hop polyphenolic groups. The acidity effect on the polyphenol was established as follows: pH 4.4 contributed to a 12% greater isoxanthohumol accumulation, while pH 5.2 promoted a six times greater accumulation of anthocyanogens than pH 4.4. The total content of polyphenols during boiling was constant and correlated with the phenolic compound in different groups. The conditions of “dry” hopping, simulating the wort clarification in Wirpool, increased the dissolution of anthocyanogens by six times in comparison with kettle hopping, which was associated with the turbulent flow. The isoxanthohumol sorption and formation rate during “dry” hopping was established when modeling the maturation conditions for different temperatures, oxygen levels, and yeast races. A lower temperature (5°C) had a negative effect on the isoxanthohumol sorption. The quercetin content was found to be in the range of 0.9–2.0 mg/dm³ at 5°C and 0.8–4.7 mg/dm³ at 20°C, which determined the temperature effect on extraction during “dry” hopping. The presence of yeast cells in the medium promoted the quercetin accumulation: the quercetin content doubled at 5°C and quadrupled at 20°C compared with the control. The rutin content in the control increased for two days, and minor fluctuations in the content of yeast cells were 5.0 ÷ 7.4 mg/dm3. A comparative analysis of the simple phenolic acids and aldehydes amounts under “dry” hopping conditions showed a greater decrease in their concentration because they were involved in the yeast consumption and biotransformation processes. Conclusion. The research made it possible to establish the phenolic compounds in various groups of migration routes under the conditions of classical (kettle) and “dry” methods of hopping, as well as their dependence on such factors as medium acidity, stirring intensity, temperature, oxygen content, and yeast race. The sorption rates of the polyphenolic compounds were established as follows: absorption of isoxanthohumol was at its highest during the first day of “dry” hopping, and that of rutin – within two days, while quercetin was not absorbed at all. Therefore, an additional fermentation stage can be considered as the most expedient method of “dry” hopping.